Pola Komunikasi Guru Dengan Anak Autisme Di Sekolah Khusus Fauzan - Fitri Yani; Khamim Zarkasih Putro; Imroatun Imroatun; Muhiyatul Huliyah (UIN Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this research is to find out the teacher's communication patterns with autistic children at the Fauzan Special School through the PECS method. The method used is descriptive qualitative research, data collection techniques using observation by observing the communication patterns of teachers and children with autistic, documentation in the form of unstructured in-depth interviews. The results of the research were carried out through phases in PECS, from these phases it can be seen how much the communication patterns of children with autistic and teachers through the use of PECS media children can acquire language vocabulary, can say and comment little by little. The conclusion from this research is that the pattern of communication between children with autism and teachers can be done through the use of PECS media, but this method must be done routinely so that eventually children can acquire language and can communicate it with their peers.